1997
DOI: 10.1046/j.1469-0705.1997.10060400.x
|View full text |Cite
|
Sign up to set email alerts
|

Early detection of reversed diastolic umbilical flow: should we offer karyotyping?

Abstract: In normal pregnancy, end-diastolic flow appears in the umbilical artery around the 13th week of gestation, with a velocity which increases progressively with advancing gestation. The detection of reversed flow in the umbilical artery, the highest expression of an increase in placental vascular resistance, is extremely uncommon in the first half of gestation and, in three of the four cases reported in the literature, there were chromosomal abnormalities. We report a new case of reversed end-diastolic flow in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
3

Year Published

1999
1999
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 0 publications
1
8
0
3
Order By: Relevance
“…This finding is even more ominous if associated with increased nuchal translucency 38 . Absent or reversed enddiastolic flow in the umbilical artery in the first half of pregnancy may have the same significance [39][40][41] . Thus, Doppler velocimetry, combined with evaluation of fetal anatomy (i.e.…”
Section: Umbilical Doppler Velocimetrymentioning
confidence: 99%
“…This finding is even more ominous if associated with increased nuchal translucency 38 . Absent or reversed enddiastolic flow in the umbilical artery in the first half of pregnancy may have the same significance [39][40][41] . Thus, Doppler velocimetry, combined with evaluation of fetal anatomy (i.e.…”
Section: Umbilical Doppler Velocimetrymentioning
confidence: 99%
“…De acordo com revisão de artigos da língua inglesa indexados no MEDLINE, até maio de 2000, existem apenas 6 casos descritos na literatura: 4 deles portavam anomalias cromossômicas [9][10][11] e 1, cardiopatia 30 . Recentemente, em junho de 2000, descrevemos o sexto e sétimo caso 13 : tratava-se de 1 triploidia e de 1 trissomia do cromossômicas 9.…”
Section: Discussionunclassified
“…Um exemplo da heterocronia nas anomalias cromossômicas é o atraso no amadurecimento funcional do miocárdio, particularmente no surgimento de unidades contráteis (sarcômeros), o que justificaria a insuficiência cardíaca precoce, demonstrada pelo aumento da TN 5 . Recentemente, alguns estudos têm demonstrado correlação entre alterações da Dopplervelocimetria arterial 4,[9][10][11][12][13] e venosa 5,[14][15][16][17][18][19] com anomalias cromossômicas. Constatou-se fluxo reverso na artéria umbilical [9][10][11]13 , A medida da TN foi aferida por meio de "corte" sagital do feto, o mesmo utilizado para a avaliação do CCN, com a coluna posteriormente localizada.…”
Section: Introductionunclassified
“…Martinez and colleagues [18] examined the umbilical artery pulsatility index and nuchal translucency measurements in the first trimester and suggested that the presence of chromosomal anomalies may be strongly suspected when an increased nuchal translucency thickening is associated with abnormally high pulsatility index of the umbilical artery. Few authors [5,17,24] reported on reversed end-diastolic flow of the umbilical artery in chromosomally abnormal fetuses between 9 and 13 weeks' gestation. Few authors [5,17,24] reported on reversed end-diastolic flow of the umbilical artery in chromosomally abnormal fetuses between 9 and 13 weeks' gestation.…”
Section: When the Use Of Doppler In Early Pregnancy Might Be Clinicalmentioning
confidence: 99%